4-Hydroxyderricin Isolated from the Sap of Angelica keiskei Koidzumi: Evaluation of Its Inhibitory Activity towards Dipeptidyl Peptidase-IV - Diah Lia Aulifa; I Ketut Adnyana; Jutti Levita; Sukrasno Sukrasno (MDPI AG, 2019)
Angelica keiskei sap is used as a blood-sugar reducer in Indonesia, however its molecular mechanism has not yet been explored. 4-hydroxyderricin (4-HD) is one of the major components extracted from A. keiskei sap. The aim of this work was to isolate 4-HD from the sap of A. keiskei planted in Lombok, Indonesia, and to study in silico and in vitro mechanisms against dipeptidyl peptidase-IV (DPP-IV). The dried sap was submitted to liquid−liquid extraction using solvents with different polarity. Further purification processing was conducted using gradient elution column chromatography. The isolated compound was a yellowish powder, m/z 339.2215 [M + H]+, which was confirmed as 4-HD. Sitagliptin, a DPP-IV inhibitor, was employed as the positive control for both the in silico and in vitro studies. It was indicated that 4-HD interacts with Glu206 and Phe357, important amino acid residues in the DPP-IV binding pocket. These interactions are similar to that of sitagliptin. The affinity of 4-HD (inhibition constant (Ki) = 3.99 μM) to DPP-IV is lower than that of sitagliptin (inhibition constant (Ki) = 0.17 μM). Furthermore, in vitro study showed that 4-HD inhibits DPP-IV (IC50 = 81.44 μM) weaker than for sitagliptin (IC50 = 0.87 μM). We concluded that 4- HD might have potential in inhibiting DPP-IV. However, by considering the polar interaction of sitagliptin with DPP-IV, a further structure modification of 4-HD, e.g., by introducing a polar moiety such as a hydroxyl group, might be needed to obtain stronger activity as a DPP-IV inhibitor.